2014
DOI: 10.1128/genomea.01218-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Paenibacillus polymyxa CR1, a Plant Growth-Promoting Bacterium Isolated from the Corn Rhizosphere Exhibiting Potential for Biocontrol, Biomass Degradation, and Biofuel Production

Abstract: Here we report the complete genome sequence of the bacterium Paenibacillus polymyxa CR1 (accession no. CP006941), which consists of one circular chromosome of 6,024,666 bp with 5,283 coding sequences (CDS), 87 tRNAs, and 12 rRNA operons. Data presented will allow for further insights into the mechanisms underpinning agriculturally and industrially relevant processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
(16 reference statements)
0
21
0
Order By: Relevance
“…AntiSMASH analysis of the genome of strain E681, which was investigated here, revealed an equipment of 33 gene clusters involved in the synthesis of secondary metabolites, comprising four NRPS clusters ( fus , pmx , tri , and phn genes) as well as one cluster for the production of each a polyketide (Trans‐AT‐PKS‐Otherks_NRPS) according to the definition given by antiSMASH analysis with similarity to bacillaene, a lantipeptide, a lasso peptide, and a bacteriocin, which still have to be identified. Characteristic features of all these organisms are genes involved in plant‐growth promotion coding for the production of plant hormone‐like compounds, particularly indole‐3‐acetic acid, as well as volatiles, such as 3‐hydroxybutan‐2‐one and butane‐2,3‐diol . Furthermore, these organisms exhibit promising applications for biomass degradation and biofuel production …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AntiSMASH analysis of the genome of strain E681, which was investigated here, revealed an equipment of 33 gene clusters involved in the synthesis of secondary metabolites, comprising four NRPS clusters ( fus , pmx , tri , and phn genes) as well as one cluster for the production of each a polyketide (Trans‐AT‐PKS‐Otherks_NRPS) according to the definition given by antiSMASH analysis with similarity to bacillaene, a lantipeptide, a lasso peptide, and a bacteriocin, which still have to be identified. Characteristic features of all these organisms are genes involved in plant‐growth promotion coding for the production of plant hormone‐like compounds, particularly indole‐3‐acetic acid, as well as volatiles, such as 3‐hydroxybutan‐2‐one and butane‐2,3‐diol . Furthermore, these organisms exhibit promising applications for biomass degradation and biofuel production …”
Section: Discussionmentioning
confidence: 99%
“…Characteristic features of all these organisms are genes involved in plant‐growth promotion coding for the production of plant hormone‐like compounds, particularly indole‐3‐acetic acid, as well as volatiles, such as 3‐hydroxybutan‐2‐one and butane‐2,3‐diol . Furthermore, these organisms exhibit promising applications for biomass degradation and biofuel production …”
Section: Discussionmentioning
confidence: 99%
“…Paenibacillus polymyxa and P. macerans were reported to suppress the AM fungus Glomus intraradices in the rhizosphere of cucumber plants in a greenhouse experiment by Larsen et al (2009). Eastman et al (2014) reported that only three strains of P. polymyxa genomes, those of P. polymyxa E681 (NC_014483), P. polymyxa SC2 (NC_014622), P. polymyxa M1 (NC_017542) have been completely sequenced. They investigated genome sequence of P. polymyxa CR1, PGPR isolated from the corn rhizosphere exhibiting potential for biocontrol and biomass degradation.…”
Section: Paenibacillus Polymyxamentioning
confidence: 99%
“…Characteristics that distinguish the genus Paenibacillus from other members of Bacillus includes, rod-shaped bacterial cells with a flagellum; producing ellipsoidal spores with swollen sporangia; positive for catalase; negative for H 2 S production; variable for oxidase; G + C content of their DNA ranging between 45% and 54 mol%, with anteiso-C15: 0 as the major cellular fatty acid, meso-diaminopimelic acid as the diagnostic diamino acid, and more than 89.6% intra-genus similarity in 16s rRNA gene sequences (Ash et al, 1993). Paenibacillus polymyxa (formerly Bacillus polymyxa) is most widely studied strain from this genus; it has ability to fix nitrogen and capable of producing antibiotic named polymyxin, and it is widely used as biocontrol agent for control of phytopathogens in agriculture (Eastman, Weselowski, Nathoo, & Yuan, 2014). Microbes are considered as a major resource for agricultural applications (Patel, Jha, Tank, & Saraf, 2011); however, strains other than P. polymyxa belonging to this genus are poorly studied for their role in agriculture.…”
Section: Introductionmentioning
confidence: 99%